Research on Educational Leadership and Management in China since 2000s: A Systematic Literature Review - Zhang, Yuting (Research in educational administration & leadership, 2025)
Reviews providing an overview of literature regarding educational leadership and management (EDLM) that synthesize Chinese research and practice in recent years were rare. Thus, we conduct a review study focusing on EDLM in China in a systematic approach. This article aims to describe research concerning publication volume, authorship, research topics, research methodologies, and practice features involving contextual intervention, leader’s role, and leader-follower interaction. PRISMA was used in the source identification and data extraction from two international databases and “core” journals in this field. In total, 196 journal articles were included for analysis in the period between 2000 and 2023. This review draws a holistic picture of major patterns of knowledge production by exploring key Chinese characteristics and highlighting the connections and differences compared to similar reviews in other countries or regions. Notably, the findings identified that more than half of the studies had been published in the past three years, indicating that the Chinese literature in EDLM is mainly contemporary and similar to that of other Asian and developing countries. This study contributes to the landscape of leadership and management in China and connects it to the international literature, which provides sustaining power for the EDLM knowledge base.